Molecular Cloning and Characterization of a Novel Antimicrobial Peptide from the Skin of Kaloula pulchra - Gao, Yahua; Chai, Jinwei; Wu, Jiena; Zeng, Qingye; Guo, Ruiyin; Chen, Xin; Xu, Xueqing (Current Pharmaceutical Biotechnology, 2022)
Background: Bacterial resistance to all currently available conventional antibiotics has caused a global public health crisis and led to an imperative search for new agents. Antimicrobial peptides (AMPs) are essential components of host innate immune defense against microbial invasions. Objectives: The objective of this study was to report a novel AMP, brevinin-2KP, from the skin of the black Kaloula pulchra frog and describe its structural and biological characterization. Materials and Methods: The physical and chemical parameters of brevinin-2KP were predicted with the ExPASy Bioinformatics Resource Portal. The assembled sequences were aligned with ClustalW, and the phylogenetic tree was constructed using Mega. Circular dichroism (CD) experiments were carried out to identify the secondary structure and the stability of peptide in different solvent environments. The cytotoxicity of brevinin-2KP was evaluated by the MTT test. To determine antibacterial activity of brevinin- 2KP, a standard two-fold broth dilution method was used. SEM was carried out to observe the morphological change in the bacterial treated by brevinin-2KP. The live/dead bacterial viability was measured with a LIVE/DEAD® BacLight kit. Histamine release and mast cell degranulation assays were performed. Results: The precursor of brevinin-2KP contains 72 amino acid residues, including a conserved signal peptide, acidic propeptide with KR residues, and mature peptide with a sequence of GVITDALKGAAKTVAAELLKKAHCKLTNSC. Phylogenetic analysis based on the amino acid sequences of 34 brevinin-2 peptides from 30 anuran species demonstrates that K. pulchra is genetically closely related to the genus Hylarana. The CD spectra analysis indicates that brevinin-2KP adopts random coil in the water and an organized α-helical conformation in SDS solution. Further, this secondary structure is stable under high salt and high-temperature conditions. Brevinin-2KP is weakly active towards the tested Gram-positive and Gram-negative bacteria as well as fungi due to its membranolytic action. Moreover, brevinin-2KP inhibits the proliferation of several mammal cells with IC50 values ranging from 3.27 to 59.75 μM. In addition, brevinin-2KP promotes degranulation and histamine release of mast cells, indicating that it is involved in the inflammatory response. Conclusion: This is the first report on AMP identified from the skin of K. pulchra. Brevinin-2KP adopts a typical amphipathic α-helix conformation in membrane mimic environment and shows antimicrobial and antitumor activities by potential membranolytic mechanism. In addition, brevinin-2KP can promote degranulation and histamine release of mast cells. Brevinin-2KP is expected to become a good drug temple molecule.
Keywords: amphibian